The bounty - Evanovich, Janet; Hamilton, Steve, 1961- (Evanovich, Janet. Fox and O'Hare novels., 2021)
Straitlaced FBI agent Kate O'Hare and international con man Nick Fox reluctantly team up with the fathers who taught them everything they know to prevent a shadowy international organization from claiming a fortune in Nazi gold.